Physical profile of junior and senior amateur boxers - Wilson, D. C.; Ruddock, A. D.; Ranchordas, M. K.; Thompson, S. W.; Rogerson, D. (Boxing Science, 2020)
The purpose of this study was to profile the physiological characteristics of amateur boxers using a battery of tests designed to assess the physiological demands required for performance. Fifteen junior amateur (age 14.9 ±2.0 years; stature 164±12 cm; bodymass 50.9±11.3 kg) and sixteen senior amateur boxers (n = 16; age 20.5±4.0 years; stature 174±9 cm; bodymass 65.2±10.7 kg) provided informed consent to participate in the study. Body composition, squat jump (SJ), countermovement jump (CMJ), 5-and 10 m sprint (5SP/10SP), press up (PU), right and left medicine-ball single-arm throws (MBR, MBL), repeated sprint test (RST) and Yo-Yo intermittent recovery test level 1 (YY) were performed. The likelihood (% chance) of between-group differences wereassessed using a magnitude based approach, standardised-difference score (Cohen`s d) and 90% confidence intervals [CI]. Linear regression (r) was used to examine association between variables. Senior boxers outperformed (79 to 99% chance) junior counterparts in PU, YY, CMJ, SJ, 10SP, MBL and MBR tests (d =0.50 [-0.34 to 1.61]). There were very large (r =0.70) correlations between fat free mass, upper-and lower body lean mass and medicine ball throw distance. There were large correlations (r=0.50 to 0.69) between medicine ball throw distance and CMJ, SJ, PU, 5SP and 10SP. A simple and time-effective test battery was able to differentiate performance between junior and amateur boxers. These assessments could be useful when profiling junior and senior amateur boxers.